Clever Tax Planning & Performance: Insight From Construction Companies Subject Final Income Tax - Suharyono, Suharyono (Universitas Ibn Khladun Bogor, 2024)
This study aims to analyze and evaluate the benefits of tax planning in a construction company, where income tax is subject to Final Income Tax (the size of costs does not affect taxation). This study employs a qualitative method with an ethnomethodology and case study approach, and data collection is conducted through observation and in-depth interviews. Observation activities are carried out in the Accounting department (responsible for tax audits and document inspections), the Finance department (responsible for VAT and Income Tax articles 4, 23, 22), HRD (responsible for Income Tax 21, non-monetary benefits, and vehicles), and the Internal Audit department (responsible for samples projects). The results of this study indicate that tax avoidance can enhance company performance, whether through motivated human resources due to the company bearing the income tax burden or increased profits due to efficiency and effectiveness. Through the findings of this study, the authors hope that tax avoidance can be executed efficiently and integrated as much as possible into the company's current processes, making it easy, and cost-effective to implement.